2016
DOI: 10.1002/ajpa.23110
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal assessment and secular changes in knee development: a radiographic approach

Abstract: The epiphyses that appear early in life, for example the distal femoral epiphysis, require gestational age information to accurately estimate appearance times. There are considerable differences between the ossification timing patterns presented in this study and those of previous standards, which did not include gestational ages. Several factors may explain the observed differences in the epiphyses of the knee including: the availability of gestational age information, the analysis of longitudinal versus cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…For instance, there is a documented secular trend in long bone lengths and terminal adult stature that overlaps with the time period of the study sites and the reference sample (Jantz & Jantz, 1999; Meadows & Jantz, 1995). This trend is also present during the developmental period with evidence of change in epiphyseal fusion timing, dental development timing, and long bone growth timing (Boeyer & Ousley, 2017; Duren et al, 2015; Malina et al, 1987; Malina & Zavaleta, 1980; Maresh, 1972; Meredith, 1976; Vucic et al, 2014). Due to such trends, one may question the appropriateness of such comparisons between the modern reference sample and the sites under study.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…For instance, there is a documented secular trend in long bone lengths and terminal adult stature that overlaps with the time period of the study sites and the reference sample (Jantz & Jantz, 1999; Meadows & Jantz, 1995). This trend is also present during the developmental period with evidence of change in epiphyseal fusion timing, dental development timing, and long bone growth timing (Boeyer & Ousley, 2017; Duren et al, 2015; Malina et al, 1987; Malina & Zavaleta, 1980; Maresh, 1972; Meredith, 1976; Vucic et al, 2014). Due to such trends, one may question the appropriateness of such comparisons between the modern reference sample and the sites under study.…”
Section: Discussionmentioning
confidence: 93%
“…This trend is also present during the developmental period with evidence of change in epiphyseal fusion timing, dental development timing, and long bone growth timing (Boeyer & Ousley, 2017;Duren et al, 2015;Malina et al, 1987;Malina & Zavaleta, 1980;Maresh, 1972;Meredith, 1976;Vucic et al, 2014). Due to such trends, one may question the appropriateness of such comparisons between the modern reference sample and the sites under study.…”
Section: Historic African American Growth In Contextmentioning
confidence: 99%
“…The change in condylar asymmetry is likely explained by the continued ossification of the distal femoral epiphysis. Boeyer and Ousley 5 found that by 3.7 weeks of life, 95% of all individuals will exhibit an ossified distal femoral epiphysis. The distal femoral epiphysis will continue to grow, forming both femoral condyles, until it completely fuses with the metaphysis between 14 and 16 years of age in women and 16 and 18 years of age in men.…”
Section: Discussionmentioning
confidence: 99%
“…The Orthopaedic Journal of Sports Medicine, 12 (5), 23259671241249132 DOI: 10.1177/23259671241249132 Ó The Author(s) 2024 1 This open-access article is published and distributed under the Creative Commons Attribution -NonCommercial -No Derivatives License (https://creativecommons.org/ licenses/by-nc-nd/4.0/), which permits the noncommercial use, distribution, and reproduction of the article in any medium, provided the original author and source are credited. You may not alter, transform, or build upon this article without the permission of the Author(s).…”
mentioning
confidence: 99%